Digital Citizen and Its Relationship with State in Digital Era (in view of real instances) - Heidar Shahriari; sajad rahbar (رهیافتهای سیاسی و بین المللی)
Digital citizen is a new conception which it redefines the citizen concept in a new world, and questions the citizen's role and relationship with other phenomena of the new world. The survey of this conception is to identify the relationship of digital citizen and it's potentialities and non-potentialities with digital state in current world by suggesting some case studies (such as Coronavirus crisis, genetics, digital city and artificial intelligence), in which, the ways of digital citizen living through digital network of political power will be identified. Thereby, this writing hypothesizes that a new and reciprocal process between digital citizen and state is streaming on, in a way, that state predominantly controls the process. In other word, since the digital state perceives the citizen as a production for state's living, therefore, it tries to convince or coerces digital citizen to follow the existing political network. This research, conducted by library method, through an interactive logic for analyzing the data and in view of historical sociology, has concluded that the relationship of the digital citizen with state involves an evolutionary way, through which, the digital citizen is convinced and complied with the new state in the new era.